A high power fibre laser for electron beam emittance measurements - Corner, L; Nevay, L; Walczak, R (2010)
We present the latest results on the development of a high power fibre laser system for a laser-wire measuring electron beam emittance in an ILC-specification environment. The laser consists of a commercial Ytterbium (Yb) doped fibre laser system producing 1μJ pulses at 6.49MHz, which can be locked to an external frequency reference. This output has been amplified in a single 70cm rod type photonic crystal fibre (PCF), producing ∼ 100μJ pulses in a burst mode at 2Hz (limited by diagnostics).